2006
DOI: 10.4049/jimmunol.176.1.284
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Induces Myeloid-Derived Suppressor Cells that Facilitate Tumor Progression

Abstract: Epidemiological and experimental observations support the hypothesis that chronic inflammation contributes to cancer development and progression; however, the mechanisms underlying the relationship between inflammation and cancer are poorly understood. To study these mechanisms, we have transfected the mouse 4T1 mammary carcinoma with the proinflammatory cytokine IL-1β to produce a chronic inflammatory microenvironment at the tumor site. Mice with 4T1/IL-1β tumors have a decreased survival time and elevated le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
453
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(479 citation statements)
references
References 35 publications
22
453
1
3
Order By: Relevance
“…The expression of genes encoding inducible NO synthase (iNOS), arginase-1 (Arg-1), vascular endothelial growth factor, matrix metallopeptidase 9 (MMP9), S100A8, and S100A9 were quantitatively measured and compared with the mRNA expression of the housekeeping gene GAPDH. According to previously published data, iNOS and Arg-1 gene expression are elevated in MDSCs arising in several different mouse tumor models including MSC-2-, CT26-, 4T1-, and 3LL-bearing mice (15,16,(30)(31)(32). These transcripts are also reported to be considerably higher in neutrophils relative to other leukocyte populations (6,11,33).…”
Section: Cd11b + Gr-1 + Cells From Malignant Ascites Are Not Mdscsmentioning
confidence: 74%
“…The expression of genes encoding inducible NO synthase (iNOS), arginase-1 (Arg-1), vascular endothelial growth factor, matrix metallopeptidase 9 (MMP9), S100A8, and S100A9 were quantitatively measured and compared with the mRNA expression of the housekeeping gene GAPDH. According to previously published data, iNOS and Arg-1 gene expression are elevated in MDSCs arising in several different mouse tumor models including MSC-2-, CT26-, 4T1-, and 3LL-bearing mice (15,16,(30)(31)(32). These transcripts are also reported to be considerably higher in neutrophils relative to other leukocyte populations (6,11,33).…”
Section: Cd11b + Gr-1 + Cells From Malignant Ascites Are Not Mdscsmentioning
confidence: 74%
“…Recently, we showed that neutrophils expand in mammary tumorbearing K14-Cre;Cdh1 F/F ;Trp53 F/F mice because of increased macrophage-derived IL-1β stimulation of the IL-17-G-CSF axis 26 . Ectopic overexpression of IL-1β in tumors derived from cancer cell lines or a genetically engineered gastric cancer model also increases the number of circulating neutrophils [60][61][62][63] . As such, aberrant production of cytokines by tumors or stromal cells can offset the balance of neutrophil retention and release from the bone marrow.…”
Section: Neutrophil Retention and Release From Bone Marrowmentioning
confidence: 99%
“…Previous studies have demonstrated that various proinflammatory mediators, such as IL-1b (22,40), IL-6 (23), the bioactive lipid PGE 2 (24), S100A8/A9 (25,41), and complement component C5a (42), are involved in the accumulation and activation of MDSCs in tumor-bearing mice and cancer patients. However, whether TNFa, as a prototype and key proinflammatory cytokine, is also in- volved in this pathological process is still obscure.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, the cell surface phenotype of MDSCs is identified as CD11b + and Gr-1 + . The expansion of MDSCs can be induced by the stimulatory factors of myelopoiesis such as GM-CSF, stem cell factor, and vascular endothelial growth factor (19)(20)(21), released primarily by tumor cells, and the activation of MDSCs is associated with proinflammatory mediators, including IL-1b, IL-6, PGE 2 , and S100A8/9 proteins (22)(23)(24)(25), produced by tumor cells, tumor stroma, and tumor-infiltrating immune cells. For example, IL-1b has been reported to promote tumor progression by increasing the accumulation of MDSCs (22), whereas IL-1R-deficient mice have a delayed accumulation of MDSCs and reduced tumor progression.…”
mentioning
confidence: 99%